Rancang bangun lift sederhana berbasis STEM (science technology, engineering, and mathematics) pada konsep hukum newton - Andriani, Sinta; Sohibun; Azra, Azmi (Jurnal Pendidik Indonesia, 2022)
The purpose of researching these was to design a simple elevator learning media based on Science, Technology, Engineering, and Mathematics (STEM) and test the feasibility of the learning media to explain Newton’s legal concept. This research was manipulation research. The design of this device consists of three main components: acrylic, dynamos and Arduino Uno. Validation of the feasibility of the tool is reviewed from the aspect of material experts, media experts and tool feasibility. Two lecturers and one teacher tested the teaching aids. The data analysis technique in this research was the descriptive analysis technique. Based on the result of the expert questionnaire calculation, the average of 89,19% with very good criteria. So it can be concluded that simple Science, Technology, Engineering, and Mathematics (STEM) based elevator learning media are very worthy of being used as a physical model to explain newton’s legal concepts.